Must there be scapegoats?: violence and redemption in the Bible - Schwager, Raymund (Gracewing, 2000)
"Schwager reverses three millennia of conventional understanding of the Bible as he argues that the God of the Old Testament is not a God of violence; the Jesus' sacrifice is not an act of appeasement of the Father; and that the suffering and death of an infinite victim is not compensation for an infinite offence against God." "In the Hebrew Bible there is a gradual revelation over the centuries of God's rejection of violence, sacrifices, and holocausts. But this revelation is rejected by the leaders of the people. The teaching of Jesus is seen as God's final message denouncing the cult of violence." "Schwager reveals Jesus as the 'necessary scapegoat' who, unlike previous scapegoat-victims, rejects all aggression and so seeks to end the cycle of human violence." "This daring and unconventional view of Christology and the Hebrew Bible, set in the context of modern anthropology and psychology, builds upon the celebrated theory of Rene Girard's scapegoat mechanism, which asserts that violence is at the root of all human society - a theory that may rival the Oedipus complex in explanation of people's deepest and most destructive desires. Girard's theory is tested and validated as Raymund Schwager applies it to the Bible."--Jacket